2017
DOI: 10.3390/antiox6040096
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids from Marine Organisms: Biological Functions and Industrial Applications

Abstract: As is the case for terrestrial organisms, carotenoids represent the most common group of pigments in marine environments. They are generally biosynthesized by all autotrophic marine organisms, such as bacteria and archaea, algae and fungi. Some heterotrophic organisms also contain carotenoids probably accumulated from food or partly modified through metabolic reactions. These natural pigments are divided into two chemical classes: carotenes (such as lycopene and α- and β-carotene) that are composed of hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
234
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(239 citation statements)
references
References 180 publications
(217 reference statements)
1
234
0
4
Order By: Relevance
“…Singh and Gabani highlighted the importance of studying UV‐resistant microbes and their metabolites as source for potential therapeutics. Some examples are as follows: (1) the mycosporine‐like amino acids (MAAs) acting as a “sunscreen” for UV radiation in the wavelength range 310–365 nm are found in a wide range of microorganisms including cyanobacteria and eukaryotic algae and protect against UV‐induced DNA damage by preventing the formation of DNA dimers. They are already used as one of the compounds in UV sunscreens in the cosmetics industry and have been suggested for potential applications in the prevention of skin cancer induced by UV radiation such as melanoma .…”
Section: Resultsmentioning
confidence: 99%
“…Singh and Gabani highlighted the importance of studying UV‐resistant microbes and their metabolites as source for potential therapeutics. Some examples are as follows: (1) the mycosporine‐like amino acids (MAAs) acting as a “sunscreen” for UV radiation in the wavelength range 310–365 nm are found in a wide range of microorganisms including cyanobacteria and eukaryotic algae and protect against UV‐induced DNA damage by preventing the formation of DNA dimers. They are already used as one of the compounds in UV sunscreens in the cosmetics industry and have been suggested for potential applications in the prevention of skin cancer induced by UV radiation such as melanoma .…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids, commonly found in the yellow, orange or red pigments of higher plants, fungi and algae, are classed as antioxidant compounds that assume a key role in cell protection. In fact, the ability to quench singlet oxygen molecules, capture light and protect photosynthesis are the most relevant biological functions of carotenoids . Studies have found that carotenoids can also be isolated from some marine animals.…”
Section: Marine Animal Sourcesmentioning
confidence: 99%
“…[36] Chlorophyll-b is a green/yellow colour pigment and its maximum absorbance is 642 to 652 nm. Chlorophyll-c (19)(20)(21) is an accessory blue-greenish colour pigment with maximum absorbance from 447 to 452 nm and it can be found in many algae (marine green Ulva intestinalis and brown macroalgae Sargassum angustifolium). [37] Chlorophyll-d (22) is commonly found in plants, algae and other cyanobacteria.…”
Section: Chlorophyll and Its Derivativesmentioning
confidence: 99%
“…; Fiedor and Burda ; Galasso et al . ). Carotenoids such as β‐carotene (βcar), lycopene, astaxanthin and fucoxanthin are known to stimulate immune defences, arrest the cell cycle and induce apoptosis in various cell types.…”
Section: Introductionmentioning
confidence: 97%
“…Due to their colour and health‐promoting properties, carotenoids are applied in food, pharmaceutical, nutraceutical and cosmeceutical industries (Sandmann ; Galasso et al . ). Commercially relevant carotenoids are mainly produced by chemical synthesis (βcar, astaxanthin, lycopene) although there is increasing interest in the optimization of natural sources for the production of these compounds (bioproducts).…”
Section: Introductionmentioning
confidence: 97%